Ethical mindsets, aesthetics and spirituality: a mixed-methods approach analysis of the Australian services sector - Issa, Theodora (Curtin University, 2009)
This thesis reports on an interpretive mixed-methods approach research conducted in the Australian services sector. Deriving from two different yet related literatures on aesthetics and spirituality, this thesis focuses on the examination of ethical mindsets. Data was collected through an online survey of 223 respondents and focus groups interviews with 20 participants. Analysis of the quantitative and qualitative data suggests the presence of aesthetic spirituality and religious spirituality, along with optimism, harmony and balance, contentment, personal truth, making a difference, and interconnectedness as ethical mindsets components. Although this research does not support universal conclusions, the relationship between ethics, spirituality, and aesthetics identified in the Australian services sector might be replicated elsewhere. [cont'd].